Measurement of depth of object driven into the soil by using portable ultrasonic non-destructive digital indicating tester (pundit) - 393535 Mohamad Syahrir Mohamad Ross; Amiruddin Shaari (2008)
Project paper (Sarjana Muda Sains (Fizik Industri)) - Universiti Teknologi Malaysia, 2008